Improving Self-Efficacy and Problem Solving Ability of Prospective Mathematics Teachers through Hypermedia Augmented Reality - Andrini, Vera Septi (EDUTEC : Journal of Education And Technology, 2024)
This study aims to evaluate the effectiveness of augmented reality (AR)-based hypermedia in increasing self-efficacy and problem-solving abilities of prospective math teachers. The research design used was quasi-experimental with two groups, namely the experimental group and the control group. The experimental group received an AR-based hypermedia intervention for 8 weeks, while the control group received no intervention. Data were collected through self-efficacy questionnaires and problem-solving ability tests before and after the intervention. The results showed that AR-based hypermedia was effective in increasing the self-efficacy and problem-solving ability of prospective math teachers. There were significant differences in average self-efficacy and problem-solving ability between the experimental group and the control group after the intervention. The conclusion of the study is that AR-based hypermedia can be a valuable tool for improving the self-efficacy and problem-solving abilities of aspiring math teachers